2017
DOI: 10.1136/injuryprev-2017-042425
|View full text |Cite
|
Sign up to set email alerts
|

Fall-related mortality in southern Sweden: a multiple cause of death analysis, 1998–2014

Abstract: There is an increasing trend of deaths due to falls in southern Sweden. Further investigations are required to explain this observation particularly among elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Unintentional falls continued to be a major cause of death (29%) in China [38]. The trend in mortality from falls was similarly observed increasing among US and European data [39][40][41][42]. The fall-related mortality in Japanese older adults aged 65-74 years showed a more rapid and continuous decreasing trend, but men over 75 years did not decrease [43].…”
Section: Main Clusters Analysismentioning
confidence: 83%
“…Unintentional falls continued to be a major cause of death (29%) in China [38]. The trend in mortality from falls was similarly observed increasing among US and European data [39][40][41][42]. The fall-related mortality in Japanese older adults aged 65-74 years showed a more rapid and continuous decreasing trend, but men over 75 years did not decrease [43].…”
Section: Main Clusters Analysismentioning
confidence: 83%
“…In this study, 'other unintentional injuries' included hip, femur and other limb fractures for which the cause was unspecified and can include injuries consecutive to simple falls. Falls are a major external cause of mortality in many countries, especially among the elderly 33,34 . In light www.nature.com/scientificreports/ of this, falls among the elderly may therefore be under-estimated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Having complete death registration data is particularly important when concerned with assessing multiple causes of death. For example, recent studies demonstrated how a multiple-cause-of-death approach is useful to characterise the contribution of diabetes ( Rodriguez et al , 2019 ) and falls ( Kiadaliri et al , 2019 ) to mortality. Here, we assessed the utility of contributory cause of death versus underlying cause of death using the example of smoking as a risk factor for cause-specific mortality.…”
Section: Discussionmentioning
confidence: 99%